Handbook on the New Testament use of the Old Testament : exegesis and interpretation - Beale, G. K. (Gregory K.), 1949- (Grand Rapids, MI : Baker Academic, 2012)
"This concise guide by a leading New Testament scholar helps readers understand how to better study the multitude of Old Testament references in the New Testament. G. K. Beale, coeditor of the bestselling Commentary on the New Testament Use of the Old Testament, focuses on the 'how to' of interpreting the New Testament use of the Old Testament, providing students and pastors with many of the insights and categories necessary for them to do their own exegesis. Brief enough to be accessible yet thorough enough to be useful, this handbook will be a trusted guide for all students of the Bible" -- Publisher description.
Challenges to interpreting the use of the Old Testament in the new -- Seeing the Old Testament in the new: definitions of quotations and allusions and criteria for discerning them -- An approach to interpreting the Old Testament in the new -- Primary ways the New Testament uses the Old Testament -- Hermeneutical and theological presuppositions of the New Testament writers -- The relevance of Jewish backgrounds for the study of the Old Testament in the new: a survey of the sources -- A case study illustrating the methodology of this book.
Includes bibliographical references (p. 149-162) and indexes.
Keywords: Bible. -- Relation to the Old Testament; Bible. -- Quotations in the New Testament; Bible -- Hermeneutics